2014
DOI: 10.1111/gcb.12642
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and winter temperature predict long‐term range‐scale abundance changes in Western North American birds

Abstract: Predicting biodiversity responses to climate change remains a difficult challenge, especially in climatically complex regions where precipitation is a limiting factor. Though statistical climatic envelope models are frequently used to project future scenarios for species distributions under climate change, these models are rarely tested using empirical data. We used long-term data on bird distributions and abundance covering five states in the western US and in the Canadian province of British Columbia to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 118 publications
6
108
2
Order By: Relevance
“…We found strong spatial autocorrelation for each drought index but minimal spatial autocorrelation of model residuals, both of which are consistent with other studies that have investigated weather or climate impacts on wildlife (e.g., Albright, Pidgeon, Rittenhouse, Clayton, Wardlow, et al, 2010;Illán et al, 2014). We found strong spatial autocorrelation for each drought index but minimal spatial autocorrelation of model residuals, both of which are consistent with other studies that have investigated weather or climate impacts on wildlife (e.g., Albright, Pidgeon, Rittenhouse, Clayton, Wardlow, et al, 2010;Illán et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found strong spatial autocorrelation for each drought index but minimal spatial autocorrelation of model residuals, both of which are consistent with other studies that have investigated weather or climate impacts on wildlife (e.g., Albright, Pidgeon, Rittenhouse, Clayton, Wardlow, et al, 2010;Illán et al, 2014). We found strong spatial autocorrelation for each drought index but minimal spatial autocorrelation of model residuals, both of which are consistent with other studies that have investigated weather or climate impacts on wildlife (e.g., Albright, Pidgeon, Rittenhouse, Clayton, Wardlow, et al, 2010;Illán et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also tended to focus on raw climatic variables to assess bird responses to precipitation variability (e.g., Bateman et al, 2016;Illán et al, 2014). However, using metrics that more comprehensively capture deviations from average moisture conditions, such as the Standardized Precipitation Evapotranspiration Index ("SPEI"), may also reveal important patterns.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence also suggests that morphological changes are a common response to altered climates (7,8). However, despite some clear cases of climate-caused alterations of local population dynamics (9,10), multi-species, large-scale analyses of population responses to global climate change are rare (11,12).…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, precipitation can affect bird populations directly through the survival of offspring [77,78], indirectly changing the abundance or availability of invertebrates [28], flowering and fruiting of plant species, and through their impact on the vegetation structure [79]. Illán [80] studied birds of western North America, and highlighted that precipitation was one of the main determinants in the distribution patterns of land birds. Sousa et al [81] studied birds in the Catimbau National park (Caatinga area) and found strong difference between the richness of birds between the dry and the rainy seasons.…”
Section: Discussionmentioning
confidence: 99%